The neuronal adaptor protein X11alpha reduces Abeta levels in the brains of Alzheimer's APPswe Tg2576 transgenic mice. - MCLOUGHLIN, DECLAN (American Society for Biochemistry and Molecular Biology, 2003)
Increased production and deposition of the 40?42- amino acid beta-amyloid peptide (Abeta) is believed to be central to the pathogenesis of Alzheimer?s disease. A is derived from the amyloid precursor protein (APP), but the mechanisms that regulate APP processing to produce Abeta are not fully understood. X11beta (also known as munc-18-interacting protein-1 (Mint1)) is a neuronal adaptor protein that binds APP and modulates APP processing in transfected non-neuronal cells. To investigate the in vivo effect of X11beta on Abeta production in the brain, we created transgenic mice that overexpress X1beta and crossed these with transgenics harboring a familial Alzheimer?s disease mutant APP that produces increased levels of Abeta (APPswe Tg2576 mice). Analyses of Abeta levels in the offspring generated from two separate X11beta founder mice revealed a significant, approximate 20% decrease in Abeta(1?40) in double transgenic mice expressing APPswe/X11beta compared with APPswe mice. At a key time point in Abeta plaque deposition (8 months old), the number of A plaques was also deceased in APPswe/X11beta mice. Thus, we report here the first demonstration that X11beta inhibits Abeta production and deposition in vivo in the brain.
PUBLISHED The abbreviations used are: A, -amyloid peptide; APP, amyloid precursor protein; MOPS, 3-(N-morpholino)propanesulfonic acid; TBS, Tris-buffered saline; ELISA, enzyme-linked immunosorbent assay.
Keywords: Psychiatry